Beyond “Hero-based” Management: Revisiting HRM Practices for Managing Collective Expertise - Lelebina, Olga; Gand, Sébastien (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2018)
While expert knowledge is a crucial resource for large science-based companies, management of the specific population of experts remains a sensitive issue for the HRM. In order to recognize and retain these employees, companies traditionally implement a dual ladder—a career management tool that proposes an alternative technical career track to the managerial one, thus allowing recognition of an expert status in the organization. However, multiple studies have demonstrated that the implementation of a dual ladder does not bring the expected results. While previous research has investigated the individual aspirations of experts as possible reasons for their dissatisfaction with this managerial tool, we show the importance of the collective dimension of expertise and claim that the latter is insufficiently supported by HRM practices.Drawing on a case study in a large multinational firm, we explore the consequences of individualized practices on expert work and discuss the role of HRM in dealing with so-called “hero-based” management. The findings show that individualized practices could endanger the learning and innovation capacities of the firm and compromise processes such as decision making and problem solving. It could also jeopardize the continuity of expertise from a long-term perspective as younger generations refuse to align with a “hero-based” culture. Despite such a strategic challenge, HR managers experience difficulties in reinforcing the collective dimension of expertise. This opens up new perspectives for the HRM function that could lead the management of experts towards new horizons by supporting the fragile equilibrium between “agency” and “communion” in expertise processes.